Hubungan Kepemimpinan Visioner Kepala Sekolah dan Kinerja Guru dengan Keefektifan Sekolah Dasar Negeri - Faizah Nur Amalia; Maisyaroh Maisyaroh; R. Bambang Sumarsono; Faizah Nur Amalia; Maisyaroh Maisyaroh (Universitas Negeri Malang, 2021)
Abstract: The aim of this study is to describe visionary leadership, teacher’s performance, school effectiveness, visionary principals' leadership relationships and school effectiveness, relationship between teacher’s performance and school effectiveness, and the principal's visionary leadership relationship and teacher’s performance with school effectiveness. This study uses a quantitative approach, with a correlation research design. Sampling uses proportional sampling and area (cluster) sampling techniques with the acquisition of 86 teachers as respondents. The technique of collecting data uses a closed questionnaire. Analysis of the data used is descriptive analysis, and hypothesis testing using Pearson Product Moment correlation analysis and multiple correlation. The results obtained by the principal's visionary leadership, teacher’s performance, and school effectiveness in the medium category, there is a relationship between visionary leadership and school effectiveness, there is a relationship between teacher performance and school effectiveness, there is a relationship between visionary leadership and teacher performance with school effectiveness at SDN Lawang, Malang. Abstrak: Tujuan penelitian ini untuk mendeskripsikan kepemimpinan visioner, kinerja guru, tingkat keefektifan sekolah, hubungan kepemimpinan visioner kepala sekolah dan keefektifan sekolah, hubungan kinerja guru dan keefektifan sekolah, serta hubungan kepemimpinan visioner kepala sekolah dan kinerja guru dengan keefektifan sekolah. Penelitian ini menggunakan pendekatan kuantitatif, dengan rancangan penelitian korelasi. Pengambilan sampel menggunakan teknik proporsional sampling dan teknik area (cluster) sampling dengan perolehan 86 guru sebagai responden. Teknik pengumpulan data menggunakan angket tertutup. Analisis data yang digunakan yaitu analisis deskriptif, dan uji hipotesis menggunakan analisis korelasi Pearson Product Moment dan korelasi berganda. Hasil penelitian diperoleh kepemimpinan visioner kepala sekolah, kinerja guru, dan keefektifan sekolah dalam kategori sedang, terdapat hubungan antara kepemimpinan visioner dan keefektifan sekolah, terdapat hubungan antara kinerja guru dan keefektifan sekolah, terdapat hubungan antara kepemimpinan visioner dan kinerja guru dengan keefektifan sekolah di SDN Kecamatan Lawang, Kabupaten Malang.